Women’s Career Paths in Hungarian Higher Education in the Light of the Bologna Process - Eszter Borsos; Ádám Gergő Kiss (DETUROPE)
In our research we investigate the Hungarian higher education, which has undergone some significant transformation over the past decades. The Bologna process has fundamentally transformed our higher education: most of the previous single and undivided trainings were transformed into a two or three-stepped ones. After the previous regime the way opened for the founding of private colleges and their accreditation, which generated, again, a number of changes: the financing side showed novelties. This can be interpreted as a response to the state’s strategy that it intends to withdraw from the financing of higher education. As a result, those young people are also included in the form of fee-paying system, who did not have access to higher education because of the narrow academic admissions. At the same time, since the nineties, women became over represented in higher education on the student side. However, to date there are few women in higher education on the management side.